Labor Market Effects of International Outsourcing: How Measurement Matters - Daniel Horgos (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2007)
As regards labor market effects of International Outsourcing, empirical studies have difficulties in confirming theoretical results. The use of different indices adds to the puzzle. The paper examines whether measurement differences are one reason for the mismatch between empirical and theoretical findings. In fact, considering the properties of various outsourcing indices and applying a panel data estimation of the effects on the within industries? wage gap in Germany, theory and empirics can be reconciled: while the wage gap increases in the aggregate, the service sector and the high skill intensive industries, it decreases in the low skill intensive industries – which is in line with theoretical findings by Arndt (1997, 1998).
urn:nbn:de:gbv:705-opus-17098
Keywords: J31; F16; 330; International Outsourcing; wage differential; Outsourcing; International; Auslandsproduktion; Messung; Lohnstruktur; Beschäftigungseffekt; Theorie; Deutschland